2020
DOI: 10.1002/pbc.28718
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utilization of blinatumomab and inotuzumab immunotherapy in children with relapsed or refractory B‐acute lymphoblastic leukemia

Abstract: Background: The treatment paradigm for patients with relapsed/refractory B-cell acute lymphoblastic leukemia (rrALL) has been revolutionized given recent clinical trials demonstrating remarkable success of immunotherapies and leading to drug approvals by United States and European agencies. We report experience with commercial blinatumomab and inotuzumab use at two North American pediatric oncology centers in children and adolescents/young adults with BALL. Procedure: Patients 0-25 years old treated with the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 36 publications
(79 reference statements)
2
27
0
1
Order By: Relevance
“…Comparable data were reported by Contreras et al [ 24 ]—neurological complications accounted for 22% (4/18 patients), of which only one was grade 4, while a lower percentage of CRS was described (6/18 patients, 33%).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Comparable data were reported by Contreras et al [ 24 ]—neurological complications accounted for 22% (4/18 patients), of which only one was grade 4, while a lower percentage of CRS was described (6/18 patients, 33%).…”
Section: Discussionsupporting
confidence: 78%
“…In the German [ 16 ] retrospective analysis, the median OS for all patients was 11.1 months (0.2–113 months), and median RFS was 6.17 months (0–18 months), with a total CR rate of 34%. Contreras et al [ 24 ] reported 18 patients treated with commercial blinatumomab; 12 of them achieved a CR (both morphological and MRD). In the Spanish study [ 25 ] 8 of 15 children (53%) reached CR with sustained MRD negativity after one cycle; median OS and RFS were 22 (range 3–41) and 8.5 months (range 0–17), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of r/r precursor B-cell ALL in pediatric patients under compassionate use with InO and blinatumomab recorded two severe infections (6.5%) that led to death [ 78 ]. Likewise, another retrospective study of children with r/r B-ALL treated with InO reported two events of severe infection (7.4%; one with IFD i.e., mucor-mycosis), that survived following bridging therapy with blinatumomab [ 19 ].…”
Section: Targeting Antigens On Lymphoid Cellsmentioning
confidence: 99%
“…Colleagues from Spain describe 27 patients treated with blinatumomab and/or inotuzumab, demonstrating that both immunotherapies can induce deep remissions, and blinatumomab can serve as an effective bridging therapy during severe infections [33]. Colleagues from Greece published their experience with nine patients with R/R ALL [34].…”
Section: Efficacymentioning
confidence: 99%